Pelatihan Desain Logo untuk UMKM dan Crafting Manik-Manik bagi Anak SD di Kelurahan Pengantungan sebagai Upaya Meningkatkan Pemberdayaan Ekonomi dan Kreativitas Komunitas - Listriyani, Dwi; Mutiya, Merlen; Apriani, Murtika; Yanti, Sabrina; Ramadhan, Gilang; Widiarti, Diyas (Jurnal EMT KITA, 2025)
This service activity summarizes Community-Based Development (CBD) activities aimed at achieving economic empowerment of local community groups and increasing the capacity of individuals, groups or communities in managing resources and solving problems independently, thereby creating sustainable independence. This activity was carried out in Pengungangan Village, Ratu Samban District, with a focus on community empowerment training. This service activity aims to increase the capacity of MSMEs through logo design training as a strategic step to strengthen product branding, as well as develop creativity and entrepreneurial spirit in elementary school age children through bead crafting training. Implementation of activities involves various approaches, including observation, interviews, and active community participation. The results show an increase in participants' skills, both in making more professional logos and in producing handicrafts with economic value. Apart from that, this program has also succeeded in increasing public awareness of the importance of branding and entrepreneurship as an effort to empower the local economy. evaluation of the implementation of service activity programs, the MSME community is still in the advanced assistance stage, so there are challenges and limited access to technology and resources. Further assistance is carried out systematically via online. This program provides a significant positive impact on society. Recommendations include developing sustainable programs, increasing technological support, and strengthening product branding for the MSME community in Penganganan sub-district.